PENGARUH PENERAPAN PENGOLAHAN LIMBAH TERHADAP PENGETAHUAN DAN PERILAKU PEMBUANGAN LIMBAH DI SENTRA INDUSTRI KERAJINAN BATIK BANYUMAS - Saudin Yuniarno; Kuswanto Kuswanto (Kesmas Indonesia, 2015)
ABSTRACTEvery industrial activity yields the main product as well as the waste. The government struggles to develop the industrial sector which is safe to the environment. it is not an easy effort considering that the home industry might find it difficult to do the waste-processing which will burden the financial matter. Therefore, it is needed the wise solution to make the industry run well and the environment keep safe. This research was aimed at knowing the effect of waste-processing implementationtowards the knowledge and attitude of disposal in the industrial centre of batik Banyumas. This research was carried out in the industrial centre of Batik Banyumas. The method of this research was Quasi Experimental with One Group Pre-test Post Test type. The treatment in this research was in a form of implementation of waste-disposal coincided with lecturing, discussion, demonstration and question and answer session as well. There were 30 craftsmen as the samples in this research. The data analysis used in this research was univariate analysis, and it was known that the majority of the respondent was females having educational background of elementary school. Mean while, by using bivariate analysis, it was known that there were the effect of knowledge (p=0.00) and attitude (p=0.00) before and after being given the treatment. In conclusion, It was not guaranteed that the effect occurred on the dependent variable was due to the treatment. Moreover, it was suggested for the upcoming research to use the design of Static Group Comparison or True Experiment.Key words: waste disposal, implementation, knowledge, attitude Kesmasindo, Volume 7( 2) Januari 2015, Hal. 145-152